Bioaccumulation of heavy metals (Cd, Pb, Cu and Zn) in Scylla serrata (Forsskal 1775) collected from Sungai Penor, Pahang, Malaysia - Yunus, Kamaruzzaman; John, Akbar; B.Z, Maryam; Khan Chowdhury, Ahmed Jalal; Saad, Shahbudin (Universiti Putra Malaysia Press, 2012)
A study was conducted to assess the bioaccumulation levels of heavy metals (copper, zinc, cadmium and lead) in different body parts (carapace, claw, walking legs and intestinal tract) of the common mud crab Scylla serrata collected from Sungai Penor, Pahang, on January 2009. Accumulation of metal was determined using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Average Cu concentrations in carapace, claws, walking legs and gut were 43.83 ± 16.43μgg-1, 21.54 ± 7.14μgg-1, 28.2 ± 12.76μgg-1 and 57.06 ± 13.47μgg-1, respectively. Meanwhile, average Zn concentrations in carapace, claws, walking legs and gut were 387.38 ± 17.89μgg-1, 376.62 ± 21.91μgg-1, 361.92 ± 26.68μgg-1 and 496.31 ± 20.59μgg-1, respectively. Since Zn and Cu are the precursors of most enzymatic activities, all the body parts have significantly higher tendency to accumulate Zn and Cu. It was apparent that Zn concentration was higher in crab body parts, followed by Cu. It was also observed that intestinal track had higher levels of metals than other body parts. Since high calcium content inhibits lead uptake into the gut, a large portion of the lead burden was sequestered in the carapace. Average Pb concentrations in carapace, claws, walking legs and gut were observed to be 7.17 ± 0.46μgg-1, 6.27 ± 0.75μgg-1, 6.52 ± 0.37μgg-1 and 2.27 ± 0.82μgg-1, respectively. Among the analyzed heavy metals, Cd concentration was low in all the body parts of the crab. Average Cd concentrations in carapace, claws, walking legs and gut were 0.68 ± 0.05μgg-1, 0.42 ± 0.05μgg-1, 0.35 ± 0.04μgg-1 and 0.13 ± 0.05μgg-1, respectively. Exoskeleton absorbs higher level of Cd than internal gut region, but the accumulation of Pb was higher in gut region than the exoskeleton of the crab. It was evident from this study that all the heavy metal (Cd, Pb, Cu and Zn) accumulations in Scylla serrata were higher than the international standard Maximum Permissible Level (MPL). Hence, a detailed investigation needs to be addressed on this issue to determine the pollution status in crabs inhabiting along the Sungai Penor waters.